1974
DOI: 10.1029/ja079i028p04246
|View full text |Cite
|
Sign up to set email alerts
|

Initial ion composition results from the Isis 2 satellite

Abstract: Isis 2 satellite carried, among other ionospheric instruments, an ion mass spectrometer designed to measure the composition of the ionosphere in the mass range 1–64 amu. The satellite, in a nearly constant 1400‐km orbit, was launched on April 1, 1971. Examples of data show a wide variation in ion composition from 99% H+ at night near the equator to greater than 95% O+ (and N+) in the daytime poleward of the plasmapause. Both H+ and He+ are observed to be streaming outward from the high‐latitude regions with ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
89
0

Year Published

1975
1975
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(105 citation statements)
references
References 9 publications
16
89
0
Order By: Relevance
“…the Dst index). These features are found to occur at all longitudes, and during periods when the entire flux tube is sunlit, in comparison with the results presented by Hoffman et al (1974), which showed regions of He + dominance for partially lit flux tubes. Figure 5 shows examples of orbits during June 1991 where He + is the dominant ion, or is close to being the dominant ion.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…the Dst index). These features are found to occur at all longitudes, and during periods when the entire flux tube is sunlit, in comparison with the results presented by Hoffman et al (1974), which showed regions of He + dominance for partially lit flux tubes. Figure 5 shows examples of orbits during June 1991 where He + is the dominant ion, or is close to being the dominant ion.…”
Section: Introductionsupporting
confidence: 78%
“…Taylor et al, 1970;Paresce et al, 1974;Murphy et al, 1979;Naghmoosh and Murphy, 1983;Chandler and Chappell, 1986;Newberry et al, 1989;Moffett et al, 1989;Bailey and Sellek, 1990;Heelis et al, 1990;Richards et al, 1991;Bailey and Sellek, 1992;Gonzalez and Sulzer, 1996), and the high-latitude region (e.g. Hoffman et al, 1974;Raitt et al, 1978;Heelis et al, 1981;Quegan et al, 1984). Theoretical progress was made by Quegan et al (1981) who extended the transport equations first derived by Schunk (1975) by providing the mathematical formulation which allowed He + to be included as a major ion in a fully-ionised, four-component plasma (electrons and the O + , H + and He + ions).…”
Section: Introductionmentioning
confidence: 99%
“…Since the first measurements of the polar wind, a number of different spacecraft have probed the high-latitude ion outflows close to their outflow region in the ionosphere. ISIS 2 confirmed the outflow of H + , but also found evidence for outflows of He + and O + (Hoffman et al, 1974;Hoffman and Dodson, 1980). With DE-1 the first extensive studies of the polar wind were made (Nagai et al, 1984;Chandler et al, 1991).…”
Section: Introductionmentioning
confidence: 82%
“…(after Dyson and Winningham [1974]; see also Heikkila and Winningham [1971]). (sec) (after Hoffman [1974]; see also Hoffman et al, 1974). IMP 7 is in the morning sector at 34 R E Note the strong antisunward streaming of plasma at IMP 7 during 2200 to 2300 U.T.…”
Section: Epiloguementioning
confidence: 99%